Pengaruh Gaya Mengajar Terhadap Kedisiplinan Siswa di SD Negeri 02 Lubuak Alai - Gladis Aprilia Rahayu (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to evaluate the influence of teaching style on student discipline at SD Negeri 02 Lubuak Alai. The method used is quantitative research with data collection through questionnaires distributed to teachers at the school. The research sample was selected purposively based on certain criteria. The collected data were analyzed using descriptive and inferential statistical techniques to test the relationship between teaching style and student discipline. The results of the analysis show a significant positive influence between teacher teaching style and student discipline. Thus, teacher teaching style plays an important role in improving student discipline at SD Negeri 02 Lubuak Alai. These findings can be a reference for teachers in implementing more effective teaching styles to shape student discipline.